Religion and Art: Rethinking Aesthetic and Auratic Experiences in 'Post-Secular' Times - Džalto, Davor (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
How can we think of the "aura" of (sacred) contexts and (sacred) works? How to think of individual and collective (esthetic/religious) experiences? What to make of the manipulative dimension of (religious and esthetic) "auratic" experiences? Is the work of art still capable of mediating the experience of the "sacred," and under what conditions? What is the significance of the "eschatological" dimension of both art and religion (the sense of "ending")? Can theology offer a way to reaffirm the creative capacities of the human being as something that characterizes the very condition of being human? This Special Issue aspires to contribute to the growing literature on contemporary art and religion, and to explore the new ways of thinking of art and the sacred (in their esthetic, ideological, and institutional dimensions) in the context of contemporary culture.